Rapid Deployment and Operation of Faith-Based Digital Social Innovation: Lessons Learned from Indonesian Church Experience - Jovita Elizabeth Abraham; Pantjar Simatupang (Cita Konsultindo Research Center, 2023)
In April to June 2020, GBI Bethel Bandung launched #Beliiniaja program, Instagram-based marketing tool, as emergency response to mitigate devastative impacts of pandemic Covid-19 on the livelihood of its members. The program was quite successful. This paper translates and describes technical practice of how #Beliiniaja program that was deployed and operated with an objective to make it widely visible and draws public attention at large to make possible replications or further development. The study was conducted using the ethnography approach supported with data interview involving 30 business entities users of the organization. It was found that the church adopted the design thinking methodology with some innovative features. First, the very rapid two-step deployment and operation as compared to six-step conventional design thinking technique. Second, collaborative scrum like operation of social enterprise that made it inclusive and continuously adaptive while in operation. Third, establishment of a social enterprise based on a normally exclusive private owned digital marketing tool. It is concluded that churches and faith-based community in general could have potential capability as an agent of social digital innovations that its utilization should be encouraged for building community resilience against disasters as well as for helping improve the community members’ welfare.